Unsociability, Peer Rejection, and Loneliness in Chinese Early Adolescents: Testing a Cross-Lagged Model. (June 2021) - Xiao, Bowen; Bullock, Amanda; Liu, Junsheng; Coplan, Robert
In this study, we explored the longitudinal linkages among Chinese early adolescents' unsociability, peer rejection, and loneliness. Participants were N = 445 primary school students in Shanghai, P.R. China followed over 3 years from Grades 6 and 7 to Grades 8 and 9. Measures of adolescents' unsociability, peer rejection, and loneliness were obtained each year from a combination of self-reports and peer nominations. Among the results, (1) compared with the unidirectional and bidirectional models, the cross-lagged model was deemed the best fit for the data; (2) adolescent unsociability contributed to later increases in loneliness via a pathway through peer rejection; and (3) loneliness directly contributed to later increases in unsociability. Results are discussed in terms of the implications of unsociability for Chinese adolescents' experience of peer rejection and subsequent loneliness.